Reconciliation ecology, from biological to social challenges - Denis Couvet; Frédéric Ducarme (Revue d'ethnoécologie)
Reconciliation ecology aims to preserve ordinary biodiversity through integration of ecology and social values. We define such biodiversity as an alternative to species and site specific conservation approaches, demonstrating its analytical power to understand the dynamics of biodiversity changes, its consequences, in particular in regards to the fate of regulating ecosystem services. We then examine its potential for social legitimacy through a review of philosophical and policy frameworks. We pay particular attention to the representation of ordinary biodiversity’s extrinsic values, and to the most appropriate social norms for integrating these into new practices of conservation, based on the potential of the capabilities approach.